White Student Comfort and Conflict in Experiential Racial Dialogues. (September 2019) - Maxwell, Kelly; Chesler, Mark
Background: White students are both curious and sometimes apprehensive about engaging in dialogues about race.Purpose: We investigate white university students' experience of comfort and conflict in racial interaction in inter- and intragroup dialogues.Methodology/Approach: We analyzed student papers written at the beginning and end of the dialogue as well as their post-semester interviews, for their hopes/fears, classroom racial experiences, and learnings.Findings/Conclusions: White students in two types of semester-long dialogue courses reported issues of relative comfort and conflict as they explored their own and others' racial histories and outlooks. They reported feeling safer in the white-only (intragroup) dialogues, as they learned about white culture and privilege; they also lamented not having racialized "others" to learn from. White students in the interracial (intergroup) dialogues often reported more discomfort, risk, and tension, as they learned about the impact of white culture and privilege on students of color, as well as about racism as a white problem.Implications: We draw implications for educational practice that include dissonance and conflict as stimuli for student learning and the use of experienced-based pedagogical techniques that encourage student sharing, critical reflection on narratives and encounters, and mutual participation.